A Comprehensive Literature Review for Total Hip Arthroplasty (THA): Part 2—Material Selection Criteria and Methods - Salvatore Garofalo; Chiara Morano; Luigi Bruno; Leonardo Pagnotta (Journal of Functional Biomaterials)
Total Hip Arthroplasty (THA) is a widely used surgical procedure to restore mobility and reduce pain in patients with hip joint disorders. Implant success and longevity are influenced by the selection of appropriate materials. This study presents a comprehensive literature review based on structured searches in Scopus and Web of Science, focusing on material selection criteria and methods in THA. The inclusion criteria targeted original studies and reviews addressing material properties, selection techniques, and clinical performance. A bibliometric analysis and keyword co-occurrence network were used to highlight major research themes. The review examines traditional materials such as Metal-on-Polyethylene (MoP), as well as advanced options like ceramics, composites, and Functionally Graded Materials (FGMs). Key challenges discussed include aseptic loosening, wear resistance, and stress shielding. Selection methodologies such as Multi-Criteria Decision-Making (MCDM), Weighted Properties Methods (WPM), and computational tools like Ashby charts and CES Selector are analyzed. The findings from international arthroplasty registries show that more than half of implant failures are linked to material-related factors. This study therefore aims to guide material selection processes in THA by aligning clinical performance with biomechanical and biological requirements, supporting improved implant outcomes and long-term surgical success. Future developments should focus on patient-specific solutions and continuous innovation.